2022
DOI: 10.1589/jpts.34.161
|View full text |Cite
|
Sign up to set email alerts
|

The effect of stretching exercises on the fibre angle of the vastus lateralis and vastus medialis oblique: an ultrasound study

Abstract: [Purpose] To investigate the effects of a seven-week quadriceps stretching program on the muscle fibre orientation of the vastus medialis oblique and vastus lateralis in the lower limbs by ultrasound imaging. [Participants and Methods] Twenty-seven healthy, physically fit, asymptomatic females and males (age 21.5 ± 1.3, Tegner activity level score ≥4) were recruited. Their initial vastus medialis oblique and vastus lateralis fibre angles were determined using ultrasound. They then undertook a seven-week quadri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…18 Treatment options for PFP include physiotherapy aimed at strengthening the VM, where VMO insufficiency is implicated, stretching exercises targeting the VL in cases of VL hypertrophy, or myofascial release where myofascial restrictions are identified. 16 Previous studies have shown that it is possible to manipulate the pennation angle of the VMO and VL, either increasing the fiber angle with targeted exercises 19,20 or reducing the angle by stretching, 21 which has obvious implications for patellar tracking.…”
Section: Introductionmentioning
confidence: 99%
“…18 Treatment options for PFP include physiotherapy aimed at strengthening the VM, where VMO insufficiency is implicated, stretching exercises targeting the VL in cases of VL hypertrophy, or myofascial release where myofascial restrictions are identified. 16 Previous studies have shown that it is possible to manipulate the pennation angle of the VMO and VL, either increasing the fiber angle with targeted exercises 19,20 or reducing the angle by stretching, 21 which has obvious implications for patellar tracking.…”
Section: Introductionmentioning
confidence: 99%